1976
DOI: 10.1080/00207217608920586
|View full text |Cite
|
Sign up to set email alerts
|

Design of active R filters using only resistors and operational amplifiers

Abstract: Active filters car1 be designed using only resistors and amplifiers as the circuit elements. The reactance for these filters is obtained from the parasitic capacitances associated wit,h the amplifiers. The resonant frequency and Q of the poles and t.he location of the zeros can be controlled over a wide range by resistor feedback and feedforward circuits.General configuration for t,he first., second-and third-order filter building blocks may be used in cascade to achie\.e any desired filtering funct,ion. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Many circuits for realizing voltage-mode filters and immittance functions using the operational amplifier (op.-amp.) pole have been published (Soderstrand 1976, Mitra and Aatre 1976, Soliman and Fawzy 1978, Nandi 1978, Ananda Mohan 1980, Saha and Nandi 1980, Schauman et al 1980, Ishida et al 1986, Tsukutani et al 1991, Siddiqi and Ahmed 1991a. However, the circuit for realizing current transfer functions using the op.-amp.…”
Section: Introductionmentioning
confidence: 94%
“…Many circuits for realizing voltage-mode filters and immittance functions using the operational amplifier (op.-amp.) pole have been published (Soderstrand 1976, Mitra and Aatre 1976, Soliman and Fawzy 1978, Nandi 1978, Ananda Mohan 1980, Saha and Nandi 1980, Schauman et al 1980, Ishida et al 1986, Tsukutani et al 1991, Siddiqi and Ahmed 1991a. However, the circuit for realizing current transfer functions using the op.-amp.…”
Section: Introductionmentioning
confidence: 94%
“…Many circuits for realizing voltage-mode transfer functions using the op.-amp. pole have been published (Soderstrand 1976, Mitra and Aatre 1976, Nandi 1978, Siddiqi and Ahmed 1991. However, there are few circuits for realizing current-mode transfer functions using the op.-amp.…”
Section: Introductionmentioning
confidence: 98%
“…The proposed circuit has employed Soderstrand's voltage-mode state variable filter (Soderstrand 1976) as a prototype. It is shown that the circuit can realize low-pass, bandpass, high-pass.…”
Section: Introductionmentioning
confidence: 99%